2005
DOI: 10.1007/s00439-005-0067-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three methods to estimate genetic ancestry and control for stratification in genetic association studies among admixed populations

Abstract: Population stratification may confound the results of genetic association studies among unrelated individuals from admixed populations. Several methods have been proposed to estimate the ancestral information in admixed populations and used to adjust the population stratification in genetic association tests. We evaluate the performances of three different methods: maximum likelihood estimation, ADMIXMAP and Structure through various simulated data sets and real data from Latino subjects participating in a gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(123 citation statements)
references
References 28 publications
(25 reference statements)
6
112
0
5
Order By: Relevance
“…Ancestry informative markers (AIMs) are genetic loci showing large geographic differentiation that can be used to determine ancestral contributions at the individual and population level (Collins‐Schramm et al, 2004; Tsai et al, 2005). Multiple different panels of AIMs to infer ancestry proportions in recently admixed populations from the Americas have been used (Galanter et al, 2012; Mao et al, 2007; Price et al 2007; Watkins et al, 2012; Yaeger et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Ancestry informative markers (AIMs) are genetic loci showing large geographic differentiation that can be used to determine ancestral contributions at the individual and population level (Collins‐Schramm et al, 2004; Tsai et al, 2005). Multiple different panels of AIMs to infer ancestry proportions in recently admixed populations from the Americas have been used (Galanter et al, 2012; Mao et al, 2007; Price et al 2007; Watkins et al, 2012; Yaeger et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Los principales refieren a la cantidad de AIMs empleada, su capacidad informativa, la elección de las poblaciones parentales y el número de individuos que integran las mismas (e.g. Tsai et al 2005). La importancia del número de marcadores utilizados consiste no solamente en su influencia sobre los resultados obtenidos, sino también porque allí radica mayormente el costo que conlleva este tipo de estudios.…”
Section: Discussionunclassified
“…Esto se condice con el hecho de que el único caso para el cual se observó que la varianza entre las cinco corridas supera a la variación entre individuos corresponde al componente subsahariano (Tabla 2). Tsai et al (2005) proponen el uso de al menos 100 marcadores para una estimación correcta. Sin embargo, los autores también indican que el número necesario disminuye a medida que aumenta la capacidad informativa, puesto que al usar AIMs con una diferencia de más de 0,5 entre las frecuencias alélicas de las poblaciones parentales, se requerirían menos de 50 marcadores para mejorar la exactitud de las estimaciones.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…This information can be used to adjust association test statistics and correct for hidden population stratification in case-control designs using self-reported ethnic membership (92)(93)(94)(95)(96). Simulation studies have demonstrated that upward of 100 AIMs are needed for optimal adjustment (97,98). For example, in a reanalysis of previously published findings based on 35 AIMs (99), Halder and colleagues selected 177 AIMs for maximum information content.…”
Section: Adjusting For Population Stratificationmentioning
confidence: 99%